Comparison of Metarhizium isolates for biocontrol of helicoverpa armigera (Lepidoptera : Noctuidae) in chickpea - Kulkarni, Shuklangi A.; Ghormade, Vandana; Kulkarni, Girish; Kapoor, Manisha; Chavan, Santosh B.; Rajendran, Armugam; Patil, Sanjay K.; Shouche, Yogesh; Deshpande, Mukund V. (Biocontrol Science and Technology, 2008)
Metarhizium isolates from soil (53) and insect hosts (10) were evaluated for extracellular production of cuticle degrading enzyme (CDE) activities such as chitinase, chitin deacetylase (CDA), chitosanase, protease and lipase. Regression analysis demonstrated the relation of CDE activities with Helicoverpa armigera mortality. On basis of this relation, ten isolates were selected for further evaluation. Subsequently, based on LT(50) of the 10 isolates towards H. armigera, five isolates were selected. Out of these five isolates, three were selected on the basis of higher conidia production (60-75 g/kg rice), faster sedimentation time (ST(50)) (2.3-2.65 h in 0.1% (w/v) Tween 80) and lower LC(50) (1.4- 5.7 x 10(3) conidia/mL) against H. armigera. Finally, three Metarhizium isolates were selected for the molecular fingerprinting using ITS sequencing and RAPD patterning. All three isolates, M34412, M34311 and M81123, showed comparable RAPD patterns with a 935G primer. These were further evaluated for their field performance against H. armigera in a chickpea crop. The percent efficacies with the three Metarhizium isolates were from 65 to 72%, which was comparable to the chemical insecticide, endosulfan (74%).
Keywords: appressorium formation; chitin deacetylase; chitinase; chitosanase; Helicoverpa armigera; Lipase; Metarhizium anisopliae; Protease

Effect of repeated in vitro sub-culturing on the virulence of metarhizium anisopliae against helicoverpa armigera (Lepidoptera : Noctuidae) - Nahar, Pallavi B.; Kulkarni, Shuklangi A.; Kulye, Mahesh S.; Chavan, Santosh B.; Kulkarni, Girish; Rajendran, Armugham; Yadav, Priya D.; Shouche, Yogesh; Deshpande, Mukund V. (Biocontrol Science and Technology, 2008)
The effect of repeated conidial sub-culturing of Metarhizium anisopliae on its virulence against Helicoverpa armigera (Hbner) was studied. The LT(50) observed against third instar larvae of H. armigera for the first sub-culture was 3.4 days; it increased to 4.5 and 5.6 days for the 20th and the 40th sub-cultures, respectively. The LT50 values after passage of the 40th sub-culture on H. armigera decreased to 4.4 and 3.7 days for the 40th (first in vivo) and the 40th (fifth in vivo) passages, respectively. Similarly, the LC(50) of M. anisopliae towards third instar larvae of H. armigera increased from the first sub-culture (0.17x10(4)) to (3.0x10(4)) for the 40th conidial transfers on potato dextrose agar and again decreased to 0.74x10(4) and 0.23x10(4) in the 40th (first in vivo) and the 40th (fifth in vivo) passage, respectively. Similar trends for LC(50) and LT(50) values were seen when sugarcane woolly aphid, Ceratovacuna lanigera Zehntner was used as a host. Significant variation in appressorium formation and cuticle-degrading enzyme production such as chitinase, chitin deacetylase, chitosanase and protease during subsequent sub-culturing and passage through H. armigera was observed. Though there was no effect on internal transcribed spacer (ITS) sequence pattern, interestingly, in randomly amplified polymorphic DNA (RAPD), significant differences in the band intensities and in the banding pattern for different sub-cultures of M. anisopliae were observed. As stable virulence towards the insect pest is desirable for commercialisation of a mycoinsecticide, such changes in virulence due to repeated in vitro transfer need to be monitored and minimised.
Keywords: appressorium formation; chitin deacetylase; chitinase; Helicoverpa armigera; in vitro sub-culturing; Lipase; Metarhizium anisopliae; Protease

Natural yeast flora of different varieties of grapes used for wine making in India - Chavan, Pradnya; Mane, Sarika; Kulkarni, Girish; Shaikh, Shamim; Ghormade, Vandana; Nerkar, Devidas P.; Shouche, Yogesh; Deshpande, Mukund V. (Food Microbiology, 2009)
The natural Saccharomyces and non-Saccharomyces yeast flora present on the grape berries significantly affect wine production. Six grape varieties, Bangalore blue, Zinfandel, Cabernet, Chenin Blanc, Sauvignon Blanc and Shiraz are being used in India for wine making. The yeast diversity was studied on the basis of morphological, colony, physiological characteristics and 5.8S-ITS sequencing of rDNA of the isolates. Eleven different species belonging to seven genera were identified as: Candida azyma, Candida quercitrusa, Debaryomyces hansenii, Hanseniaspora guilliermondii, Hanseniaspora viniae, Hanseniaspora uvarum. Issatchenkia orientalis, Issatchenkia terricola, Pichia membranifaciens, Saccharomyces cerevisiae and Zygoascus steatolyticus. H. guilliermondii was the predominant species while S. cerevisiae was observed occasionally in the six vine varieties. For the first time, C. azyma was isolated from Bangalore blue and Cabernet varieties grown in different localities. This association may be attributed to the change in cropping pattern from sugarcane to viticulture in the vine growing regions and the known association of C. azyma with sugarcane phylloplane. Further analysis of the indigenous strains and the qualitative and quantitative changes in the flora during fermentation will be useful to understand wine quality and to design preservation strategies to control wine spoilage. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: 5.8S-ITS sequence; Identification; Physiological; Wine yeasts

Draft genome of ochrobactrum intermedium strain M86 isolated from non-ulcer dyspeptic individual from India - Kulkarni, Girish; Dhotre, Dhiraj; Dharne, Mahesh S.; Shetty, Sudarshan; Chowdhury, Somak; Misra, Vatsala; Misra, Sriprakash; Patole, Milind; Shouche, Yogesh (GUT Pathogens, 2013)
Background: Ochrobactrum intermedium is an emerging opportunistic pathogen of humans that is closely related to members of the genus Brucella. Earlier, we reported the case of an Indian subject with non-ulcer dyspeptic symptoms whose urease positive gastric biopsy revealed the presence of Helicobacter pylori along with non-Helicobacter like bacteria, eventually cultured and identified as O. intermedium strain M86. Results: Here, we describe the unclosed draft genome of the strain M86 with a length of 5,188,688 bp and mean G+C content of 57.9%. We have also identified many putative gene clusters that might be responsible for its persistence in the gastric mucosa. Comparative analysis of genomic features of Ochrobactrum intermedium strain M86 and Ochrobactrum intermedium LMG 3301(T) was also done. Conclusions: This paper attempts to gain whole-genome based insights into the putative gene determinants of O. intermedium for survival in the highly acidic stomach lumen environment. Identification of genes putatively involved in the various metabolic pathways may lead to a better understanding of the survival of O. intermdedium in acidic condition.

Multilocus sequence typing of Ochrobactrum spp. isolated from gastric niche - Kulkarni, Girish (Journal of Infection and Public Health, 2017)
The human stomach is colonized by diverse bacterial species. The presence of non-Helicobacter pylori bacteria in urease-positive biopsies of individuals has been reported. Bacteria belonging to the Ochrobactrum genus have been documented in the human gastric niche. The co-occurrence of Ochrobactrum spp. with H. pylori was previously reported in an antral biopsy of a non-ulcer dyspeptic (NUD) subject from Northern India. There is no information on the genetic diversity of Ochrobactrum spp. isolated from the gastric niche in the stomach. We aimed to study the species distribution and diversity of Ochrobactrum spp. with and without H. pylori in urease-positive biopsies across three different geographical regions in India. Sixty-two Ochrobactrum isolates recovered from patients with an upper gastric disorder (n=218) were subjected to molecular identification and multilocus sequence typing. H. pylori DNA was found in the majority of biopsies, which had a variable degree of Ochrobactrum spp present. Interestingly, some of the urease-positive biopsies only had Ochrobactrum without any H. pylori DNA. Based on phylogenetic analysis, the Ochrobactrum isolates were distributed into the O. intermedium, O. anthropi and O. oryzae groups. This indicates there are multiple species in the gastric niche irrespective of the presence or absence of H. pylori. Antibiotyping based on colistin and polymyxin B could differentiate between O. intermedium and O. anthropi without revealing the resistance-driven diversity. Considering the prevalence of multiple Ochrobactrum spp. in the human gastric niche, it is important to evaluate the commensal and/or pathogenic nature of non-H. pylori bacteria with respect to their geographical distribution, lifestyle and nutrition needs.
Keywords: Helicobater Pyroli; MLST; Non-Ulcer Dyspepsia; Ochrobactrum